IMPLEMENTASI PEMBINAAN KARAKTER PESERTA DIDIK KELAS X DI SMAN 10 BOGOR - Hapso, Putri Nadia; Husni, Rahmatul (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2025)
The current educational curriculum in Indonesia pays great attention to fostering the character of students, especially through the role of Islamic Religious Education (PAI) teachers. However, the reality in the field shows that the character of students is declining, so PAI teachers are often the ones to blame for the failure. This study aims to determine the efforts made by PAI teachers in fostering the character of class X students at SMAN 10 Bogor, as well as the foundation used in the coaching process. This study used a descriptive qualitative approach, with data collection techniques in the form of observation, interviews, and documentation. The results showed that the implementation of character building is done through three approaches, namely prevention, development, and healing efforts. PAI teachers are active in providing guidance, creating a conducive environment, and providing motivation and further coaching for problematic students. The main foundation in the character building process is Merdeka Curriculum, which allows strengthening of character values and habituation through more flexible learning. In conclusion, PAI teachers play an important role in fostering students' character, but require support from various parties for optimal results.